Is maxillomandibular advancement an effective treatment for obstructive sleep apnea? Systematic literature review and meta-analysis - Trindade, Paulo Alceu Kiemle [UNESP]; Nogueira, Vania dos Santos Nunes [UNESP]; Weber, Silke Anna Theresa [UNESP] (Elsevier, 2023)
Objectives: To evaluate the effectiveness of maxillomandibular advancement surgery in the treatment of Obstructive Sleep Apnea by comparing the pre- and postoperative Apnea and Hypopnea Index, in addition to classifying the degree of evidence and risk of intervention bias. Methods: A systematic review of the literature was carried out in the PUBMED, LILACS, EMBASE, SCOPUS, WEB OF SCIENCE and COCHRANE platforms, including cohort studies with polysomnographic follow-up, without other associated pharyngeal or nasal surgical procedures. The risk of study bias was assessed using the Modified Delphi technique. Pre- and postoperative Apnea and Hypopnea Index data were plotted for meta-analysis, and the quality of evidence was assessed using the GRADE system. Results: Of 1882 references, 32 articles were selected for full-text reading, of which four studies were included, totaling 83 adults with obstructive sleep apnea who underwent maxillomandibular advancement. The meta-analysis was in favor of the intervention (DM = −33.36, 95% CI −41.43 to −25.29, p < 0.00001), with a mean percentage reduction in the Apnea and Hypopnea Index of 79.5% after surgery, even though the level of evidence was classified as very low quality by the GRADE system. Conclusion: The meta-analysis was in favor of the intervention, characterizing maxillomandibular advancement surgery as an effective treatment for obstructive sleep apnea in adults.
Keywords: Maxillomandibular advancement; OSA; Polysomnography